Effectiveness of decision support tools on reducing antibiotic use for respiratory tract infections: a systematic review and meta-analysis - Xu, Rixiang; Wu, Lang; Wu, Lingyun; Xu, Caiming; Mu, Tingyu (Frontiers in Pharmacology, 2023)
Background: Clinical decision support tools (CDSs) have been demonstrated to enhance the accuracy of antibiotic prescribing among physicians. However, their effectiveness in reducing inappropriate antibiotic use for respiratory tract infections (RTI) is controversial.Methods: A literature search in 3 international databases (Medline, Web of science and Embase) was conducted before May 31, 2023. Relative risk (RR) and corresponding 95% confidence intervals (CI) were pooled to evaluate the effectiveness of intervention. Summary effect sizes were calculated using a random-effects model due to the expected heterogeneity (I 2 over 50%).Results: A total of 11 cluster randomized clinical trials (RCTs) and 5 before-after studies were included in this meta-analysis, involving 900,804 patients met full inclusion criteria. Among these studies, 11 reported positive effects, 1 reported negative results, and 4 reported non-significant findings. Overall, the pooled effect size revealed that CDSs significantly reduced antibiotic use for RTIs (RR=0.90, 95%CI=0.85 to 0.95, I 2 =96.10%). Subgroup analysis indicated that the intervention duration may serve as a potential source of heterogeneity. Studies with interventions duration more than two years were found to have non-significant effects (RR=1.00, 95%CI=0.96 to 1.04, I 2 =0.00%). Egger's test results indicated no evidence of potential publication bias (P=0.287).Conclusion: this study suggests that CDSs effectively reduce inappropriate antibiotic use for RTIs among physicians. However, subgroup analysis revealed that interventions lasting more than two years did not yield significant effects. These findings highlight the importance of considering intervention duration when implementing CDSs.